2.2.53 Problems 5201 to 5300

Table 2.107: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

5201

\[ {}\left (3 x^{2}-y^{2}\right ) y^{\prime } = 2 x y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

4.293

5202

\[ {}\left (x^{4}+y^{2}\right ) y^{\prime } = 4 x^{3} y \]

[[_homogeneous, ‘class G‘], _rational]

2.463

5203

\[ {}y \left (1+y\right ) y^{\prime } = \left (x +1\right ) x \]

[_separable]

1.483

5204

\[ {}\left (x +2 y+y^{2}\right ) y^{\prime }+y \left (1+y\right )+\left (x +y\right )^{2} y^{2} = 0 \]

[_rational]

4.382

5205

\[ {}\left (x^{2}+2 y+y^{2}\right ) y^{\prime }+2 x = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

1.258

5206

\[ {}\left (x^{3}+2 y-y^{2}\right ) y^{\prime }+3 x^{2} y = 0 \]

[_exact, _rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

1.211

5207

\[ {}\left (1+y+x y+y^{2}\right ) y^{\prime }+1+y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational]

1.454

5208

\[ {}\left (x +y\right )^{2} y^{\prime } = a^{2} \]

[[_homogeneous, ‘class C‘], _dAlembert]

3.366

5209

\[ {}\left (x -y\right )^{2} y^{\prime } = a^{2} \]

[[_homogeneous, ‘class C‘], _dAlembert]

2.365

5210

\[ {}\left (x^{2}+2 x y-y^{2}\right ) y^{\prime }+x^{2}-2 x y+y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

7.313

5211

\[ {}\left (x +y\right )^{2} y^{\prime } = x^{2}-2 x y+5 y^{2} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

6.584

5212

\[ {}\left (a +b +x +y\right )^{2} y^{\prime } = 2 \left (a +y\right )^{2} \]

[[_homogeneous, ‘class C‘], _rational]

1.977

5213

\[ {}\left (2 x^{2}+4 x y-y^{2}\right ) y^{\prime } = x^{2}-4 x y-2 y^{2} \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

4.885

5214

\[ {}\left (3 x +y\right )^{2} y^{\prime } = 4 \left (3 x +2 y\right ) y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

18.873

5215

\[ {}\left (1-3 x -y\right )^{2} y^{\prime } = \left (1-2 y\right ) \left (3-6 x -4 y\right ) \]

[[_homogeneous, ‘class C‘], _rational]

3.251

5216

\[ {}\left (\cot \left (x \right )-2 y^{2}\right ) y^{\prime } = y^{3} \csc \left (x \right ) \sec \left (x \right ) \]

[‘y=_G(x,y’)‘]

57.221

5217

\[ {}3 y^{2} y^{\prime } = 1+x +a y^{3} \]

[_rational, _Bernoulli]

1.610

5218

\[ {}\left (x^{2}-3 y^{2}\right ) y^{\prime }+1+2 x y = 0 \]

[_exact, _rational]

1.234

5219

\[ {}\left (2 x^{2}+3 y^{2}\right ) y^{\prime }+x \left (3 x +y\right ) = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

6.238

5220

\[ {}3 \left (x^{2}-y^{2}\right ) y^{\prime }+3 \,{\mathrm e}^{x}+6 x y \left (x +1\right )-2 y^{3} = 0 \]

[‘y=_G(x,y’)‘]

2.041

5221

\[ {}\left (3 x^{2}+2 x y+4 y^{2}\right ) y^{\prime }+2 x^{2}+6 x y+y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

6.635

5222

\[ {}\left (1-3 x +2 y\right )^{2} y^{\prime } = \left (4+2 x -3 y\right )^{2} \]

[[_homogeneous, ‘class C‘], _rational]

37.298

5223

\[ {}\left (1-3 x^{2} y+6 y^{2}\right ) y^{\prime }+x^{2}-3 x y^{2} = 0 \]

[_exact, _rational]

1.554

5224

\[ {}\left (x -6 y\right )^{2} y^{\prime }+a +2 x y-6 y^{2} = 0 \]

[_exact, _rational, [_1st_order, ‘_with_symmetry_[F(x),G(x)]‘]]

1.375

5225

\[ {}\left (x^{2}+a y^{2}\right ) y^{\prime } = x y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

2.651

5226

\[ {}\left (x^{2}+x y+a y^{2}\right ) y^{\prime } = a \,x^{2}+x y+y^{2} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

23.378

5227

\[ {}\left (a \,x^{2}+2 x y-a y^{2}\right ) y^{\prime }+x^{2}-2 y a x -y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

8.805

5228

\[ {}\left (a \,x^{2}+2 b x y+c y^{2}\right ) y^{\prime }+k \,x^{2}+2 y a x +b y^{2} = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

753.956

5229

\[ {}x \left (1-y^{2}\right ) y^{\prime } = \left (x^{2}+1\right ) y \]

[_separable]

1.814

5230

\[ {}x \left (3 x -y^{2}\right ) y^{\prime }+\left (5 x -2 y^{2}\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _rational]

6.897

5231

\[ {}x \left (x^{2}+y^{2}\right ) y^{\prime } = \left (x^{2}+x^{4}+y^{2}\right ) y \]

[[_homogeneous, ‘class D‘], _rational]

1.608

5232

\[ {}x \left (1-x^{2}+y^{2}\right ) y^{\prime }+\left (1+x^{2}-y^{2}\right ) y = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

4.190

5233

\[ {}x \left (a -x^{2}-y^{2}\right ) y^{\prime }+\left (a +x^{2}+y^{2}\right ) y = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

3.996

5234

\[ {}x \left (2 x^{2}+y^{2}\right ) y^{\prime } = \left (2 x^{2}+3 y^{2}\right ) y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

14.051

5235

\[ {}\left (x \left (a -x^{2}-y^{2}\right )+y\right ) y^{\prime }+x -\left (a -x^{2}-y^{2}\right ) y = 0 \]

[[_1st_order, _with_linear_symmetries], _rational]

1.769

5236

\[ {}x \left (a +y\right )^{2} y^{\prime } = b y^{2} \]

[_separable]

1.497

5237

\[ {}x \left (x^{2}-x y+y^{2}\right ) y^{\prime }+\left (x^{2}+x y+y^{2}\right ) y = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

53.020

5238

\[ {}x \left (x^{2}-x y-y^{2}\right ) y^{\prime } = \left (x^{2}+x y-y^{2}\right ) y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

71.829

5239

\[ {}x \left (x^{2}+y a x +y^{2}\right ) y^{\prime } = \left (x^{2}+b x y+y^{2}\right ) y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

180.927

5240

\[ {}x \left (x^{2}-2 y^{2}\right ) y^{\prime } = \left (2 x^{2}-y^{2}\right ) y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

19.117

5241

\[ {}x \left (x^{2}+2 y^{2}\right ) y^{\prime } = \left (2 x^{2}+3 y^{2}\right ) y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

19.966

5242

\[ {}2 x \left (5 x^{2}+y^{2}\right ) y^{\prime } = x^{2} y-y^{3} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

20.244

5243

\[ {}x \left (x^{2}+y a x +2 y^{2}\right ) y^{\prime } = \left (a x +2 y\right ) y^{2} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

317.730

5244

\[ {}3 x y^{2} y^{\prime } = 2 x -y^{3} \]

[[_homogeneous, ‘class G‘], _exact, _rational, _Bernoulli]

2.702

5245

\[ {}\left (1-4 x +3 x y^{2}\right ) y^{\prime } = \left (2-y^{2}\right ) y \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

1.797

5246

\[ {}x \left (x -3 y^{2}\right ) y^{\prime }+\left (2 x -y^{2}\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _exact, _rational]

2.335

5247

\[ {}3 x \left (x +y^{2}\right ) y^{\prime }+x^{3}-3 x y-2 y^{3} = 0 \]

[_rational]

1.745

5248

\[ {}x \left (x^{3}-3 x^{3} y+4 y^{2}\right ) y^{\prime } = 6 y^{3} \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

2.373

5249

\[ {}6 x y^{2} y^{\prime }+x +2 y^{3} = 0 \]

[[_homogeneous, ‘class G‘], _exact, _rational, _Bernoulli]

2.777

5250

\[ {}x \left (x +6 y^{2}\right ) y^{\prime }+x y-3 y^{3} = 0 \]

[[_homogeneous, ‘class G‘], _rational]

2.201

5251

\[ {}x \left (x^{2}-6 y^{2}\right ) y^{\prime } = 4 \left (x^{2}+3 y^{2}\right ) y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

23.616

5252

\[ {}x \left (3 x -7 y^{2}\right ) y^{\prime }+\left (5 x -3 y^{2}\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _rational]

2.517

5253

\[ {}x^{2} y^{2} y^{\prime }+1-x +x^{3} = 0 \]

[_separable]

2.294

5254

\[ {}\left (1-x^{2} y^{2}\right ) y^{\prime } = x y^{3} \]

[[_homogeneous, ‘class G‘], _rational]

2.072

5255

\[ {}\left (1-x^{2} y^{2}\right ) y^{\prime } = \left (1+x y\right ) y^{2} \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.688

5256

\[ {}x \left (x y^{2}+1\right ) y^{\prime }+y = 0 \]

[[_homogeneous, ‘class G‘], _rational]

3.849

5257

\[ {}x \left (x y^{2}+1\right ) y^{\prime } = \left (2-3 x y^{2}\right ) y \]

[[_homogeneous, ‘class G‘], _rational]

5.490

5258

\[ {}x^{2} \left (a +y\right )^{2} y^{\prime } = \left (x^{2}+1\right ) \left (y^{2}+a^{2}\right ) \]

[_separable]

1.437

5259

\[ {}\left (x^{2}+1\right ) \left (1+y^{2}\right ) y^{\prime }+2 x y \left (1-y^{2}\right ) = 0 \]

[_separable]

23.314

5260

\[ {}\left (x^{2}+1\right ) \left (1+y^{2}\right ) y^{\prime }+2 x y \left (1-y\right )^{2} = 0 \]

[_separable]

2.385

5261

\[ {}\left (1-x^{3}+6 x^{2} y^{2}\right ) y^{\prime } = \left (6+3 x y-4 y^{3}\right ) x \]

[_exact, _rational]

1.757

5262

\[ {}x \left (3+5 x -12 x y^{2}+4 x^{2} y\right ) y^{\prime }+\left (3+10 x -8 x y^{2}+6 x^{2} y\right ) y = 0 \]

[_exact, _rational]

2.260

5263

\[ {}x^{3} \left (1+y^{2}\right ) y^{\prime }+3 x^{2} y = 0 \]

[_separable]

2.907

5264

\[ {}x \left (1-x y\right )^{2} y^{\prime }+\left (1+x^{2} y^{2}\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _rational]

2.133

5265

\[ {}\left (1-x^{4} y^{2}\right ) y^{\prime } = x^{3} y^{3} \]

[[_homogeneous, ‘class G‘], _rational]

3.043

5266

\[ {}\left (3 x -y^{3}\right ) y^{\prime } = x^{2}-3 y \]

[_exact, _rational]

1.374

5267

\[ {}\left (x^{3}-y^{3}\right ) y^{\prime }+x^{2} y = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

11.654

5268

\[ {}\left (x^{3}+y^{3}\right ) y^{\prime }+x^{2} \left (a x +3 y\right ) = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

201.339

5269

\[ {}\left (x -x^{2} y-y^{3}\right ) y^{\prime } = x^{3}-y+x y^{2} \]

[_exact, _rational]

1.768

5270

\[ {}\left (a^{2} x +\left (x^{2}-y^{2}\right ) y\right ) y^{\prime }+x \left (x^{2}-y^{2}\right ) = a^{2} y \]

[_rational]

1.735

5271

\[ {}\left (a +x^{2}+y^{2}\right ) y y^{\prime } = x \left (a -x^{2}-y^{2}\right ) \]

[_exact, _rational]

1.595

5272

\[ {}\left (3 x^{2}+y^{2}\right ) y y^{\prime }+x \left (x^{2}+3 y^{2}\right ) = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

69.728

5273

\[ {}\left (a -3 x^{2}-y^{2}\right ) y y^{\prime }+x \left (a -x^{2}+y^{2}\right ) = 0 \]

[_rational]

3.181

5274

\[ {}2 y^{3} y^{\prime } = x^{3}-x y^{2} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

17.324

5275

\[ {}y \left (1+2 y^{2}\right ) y^{\prime } = x \left (2 x^{2}+1\right ) \]

[_separable]

2.130

5276

\[ {}\left (3 x^{2}+2 y^{2}\right ) y y^{\prime }+x^{3} = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

82.441

5277

\[ {}\left (5 x^{2}+2 y^{2}\right ) y y^{\prime }+x \left (x^{2}+5 y^{2}\right ) = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

249.557

5278

\[ {}\left (x^{2}-x^{3}+3 x y^{2}+2 y^{3}\right ) y^{\prime }+2 x^{3}+3 x^{2} y+y^{2}-y^{3} = 0 \]

[_rational]

3.269

5279

\[ {}\left (3 x^{3}+6 x^{2} y-3 x y^{2}+20 y^{3}\right ) y^{\prime }+4 x^{3}+9 x^{2} y+6 x y^{2}-y^{3} = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

114.298

5280

\[ {}\left (x^{3}+a y^{3}\right ) y^{\prime } = x^{2} y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

10.522

5281

\[ {}x y^{3} y^{\prime } = \left (-x^{2}+1\right ) \left (1+y^{2}\right ) \]

[_separable]

2.155

5282

\[ {}x \left (x -y^{3}\right ) y^{\prime } = \left (3 x +y^{3}\right ) y \]

[[_homogeneous, ‘class G‘], _rational]

2.941

5283

\[ {}x \left (2 x^{3}+y^{3}\right ) y^{\prime } = \left (2 x^{3}-x^{2} y+y^{3}\right ) y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

5.953

5284

\[ {}x \left (2 x^{3}-y^{3}\right ) y^{\prime } = \left (x^{3}-2 y^{3}\right ) y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

13.661

5285

\[ {}x \left (x^{3}+3 x^{2} y+y^{3}\right ) y^{\prime } = \left (3 x^{2}+y^{2}\right ) y^{2} \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

7.360

5286

\[ {}x \left (x^{3}-2 y^{3}\right ) y^{\prime } = \left (2 x^{3}-y^{3}\right ) y \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

7.076

5287

\[ {}x \left (x^{4}-2 y^{3}\right ) y^{\prime }+\left (2 x^{4}+y^{3}\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _rational]

4.534

5288

\[ {}x \left (x +y+2 y^{3}\right ) y^{\prime } = \left (x -y\right ) y \]

[_rational]

1.645

5289

\[ {}\left (5 x -y-7 x y^{3}\right ) y^{\prime }+5 y-y^{4} = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

2.268

5290

\[ {}x \left (1-2 x y^{3}\right ) y^{\prime }+\left (1-2 x^{3} y\right ) y = 0 \]

[_rational]

1.634

5291

\[ {}x \left (2-x y^{2}-2 x y^{3}\right ) y^{\prime }+1+2 y = 0 \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

2.780

5292

\[ {}\left (2-10 x^{2} y^{3}+3 y^{2}\right ) y^{\prime } = x \left (1+5 y^{4}\right ) \]

[_exact, _rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

1.711

5293

\[ {}x \left (a +b x y^{3}\right ) y^{\prime }+\left (a +c \,x^{3} y\right ) y = 0 \]

[_rational]

1.795

5294

\[ {}x \left (1-2 x^{2} y^{3}\right ) y^{\prime }+\left (1-2 x^{3} y^{2}\right ) y = 0 \]

[_rational]

1.602

5295

\[ {}x \left (1-x y\right ) \left (1-x^{2} y^{2}\right ) y^{\prime }+\left (1+x y\right ) \left (1+x^{2} y^{2}\right ) y = 0 \]

[[_homogeneous, ‘class G‘], _rational]

2.158

5296

\[ {}\left (x^{2}-y^{4}\right ) y^{\prime } = x y \]

[[_homogeneous, ‘class G‘], _rational]

4.506

5297

\[ {}\left (x^{3}-y^{4}\right ) y^{\prime } = 3 x^{2} y \]

[[_homogeneous, ‘class G‘], _rational]

3.022

5298

\[ {}\left (a^{2} x^{2}+\left (x^{2}+y^{2}\right )^{2}\right ) y^{\prime } = a^{2} x y \]

[_rational]

3.842

5299

\[ {}2 \left (x -y^{4}\right ) y^{\prime } = y \]

[[_homogeneous, ‘class G‘], _rational]

4.458

5300

\[ {}\left (4 x -x y^{3}-2 y^{4}\right ) y^{\prime } = \left (2+y^{3}\right ) y \]

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

3.151